The Potential Effect of Bualuang (White Nelumbo nucifera Gaertn.) Extract on Sperm Quality and Metabolomic Profiles in Mancozeb-Induced Oxidative Stress in Male Rats - Jiraporn Laoung-on; Pimchanok Nuchniyom; Ketsarin Intui; Churdsak Jaikang; Kanokporn Saenphet; Kongsak Boonyapranai; Giatgong Konguthaithip; Nopparuj Outaitaveep; Sasitorn Phankhieo; Paiwan Sudwan (Life)
Mancozeb (MZ), an EBDC fungicide, has been found to contaminate agricultural products and cause male reproductive toxicity. The phytochemical compounds of white N. nucifera petal extract (WNPE) and its effects on metabolomic profiles and reproductive function in male rats poisoned with MZ were investigated. Seventy-two mature male Wistar rats were divided into nine groups (n = 8) and, for 30 days, were gavaged with WNPE at doses of 0.55, 1.10, and 2.20 mg/kg; were given distilled water; or were co-gavaged with MZ and WNPE. By evaluating the 1H-NMR of WNPE, myricetin, apigenin, luteolin, ferulic acid, caffeic acid, ascorbic acid, genistein, chlorogenic acid, naringenin, and ellagic acid were found, and the essential minerals were evaluated by AAS. The NMR spectra demonstrated that creatine, carnitine, ACh, and choline in WNPE were significantly higher than that in MZ. The gavaging of the rats with WNPE before poisoning them with MZ improved creatine, carnitine, acetylcholine, progressive sperm motility, sperm viability, and normal sperm morphology compared to rats who only received MZ. It was concluded that MZ had a toxicity effect on the male reproductive system via decreased metabolomic profiles, affecting sperm motility, sperm viability, and normal sperm morphology. Nevertheless, WNPE had plenty of bioactive compounds that could enhance creatine, carnitine, and acetylcholine, which are related to sperm quality in male rats. WNPE should be considered as an alternative dietary supplement that can protect against MZ toxicity and enhance sperm quality in the male rat reproductive system.